ANALISIS PENDIDIKAN AGAMA KRISTEN TERHADAP SIKAP GEREJA BAGI KELUARGA KORBAN BUNUH DIRI DI MINAHASA UTARA - Gabriela Tulung (PT. Giat Konseling Nusantara, 2026)
This thesis, entitled An Analysis of Christian Religious Education toward the Church’s Attitude toward Families of Suicide Victims in North Minahasa, investigates the increasing phenomenon of suicide in North Sulawesi, particularly in Talawaan Village, which reveals tensions between theological doctrine, social stigma, and cultural traditions. While the church often emphasizes suicide as sin, pastoral calling requires the presence of love, compassion, and accompaniment for grieving families. Employing a qualitative descriptive approach through interviews, observation, and document analysis with pastors, church elders, community leaders, and local residents, the study found that Christian Religious Education (CRE) must bridge these tensions by embodying God’s love through prayer, faith strengthening, and pastoral care. The main obstacles include rigid doctrinal views, social stigma that labels suicide as a disgrace, and discriminatory customary practices toward the deceased and their families. The findings suggest that CRE should function not merely as doctrinal transmission but as a transformative pastoral instrument that nurtures love, empathy, and solidarity within the congregation. In this way, the church can become an agent of renewal that embodies and proclaims the liberating love of Christ in society.